An indirect enzyme-linked immunosorbent assay for detecting antibody repsonse in pigs infected by emerging porcine Seneca Valley Virus - Patterson, William G.; Li, Yanhua; Fang, Ying (My University, 2017)
Seneca Valley Virus (SVV), is a single-stranded non-enveloped RNA virus. SVV belongs to the genus Senecavirus, family Picornaviridae. SVV causes gross vesicular lesions around the coronary band, snout, distal limbs, and oral mucosa. Other notable members of this family, with similar clinical presentations, include Foot and Mouth Disease (FMDV) and Swine Vesicular Disease Virus (SVDV). Due to the clinical resemblance of SVV to the more pathogenic FMDV and SVDV, a serological test is required for SVV diagnosis and differentiation. A recombinant plasmid encoding the SVV VP2 capsid protein was created using the blank PDV-His-GST plasmid. The SVV VP2 protein was designed and expressed using an E. Coli vector expression system. The recombinant VP2 protein was purified as a soluble protein using 6His-tag Ni-NTA beads, and confirmed using Western blot. The recombinant protein was tested against SVV infected piglets at 14 dpi or 21 dpi, SVV negative piglets, and mouse monoclonal antibodies against His-Tag. The ELISA test was run with different dilutions of coating antigen, serum dilutions. The most robust reaction occurred at an antigen concentration of 200ng/well, and a serum dilution of 1/20. Under these conditions, the optical density reading for the positive samples showed a high deviation from the GST protein coating, no antigen coating, and negative controls. This test shows that a recombinant SVV VP2 protein can be expressed and used to as an antigen to detect immune response in SVV infected piglets at 14 and 21 days post infection. Further validation of this ELISA test is needed, including determination of test cutoff values, diagnostic sensitivity, and diagnostic specificity, and a comparison to that of FMDV specific ELISAs. Outcomes of this study provide additional tools to aid in SVV and FMDV epidemiological surveillance and outbreak investigation.
Keywords: Fall 2017